Direction of UMPSA and Its Dedication to Environmental, Social, and Governance ESG Principles - Mohamad Akib, Baharom (UMPSA, 2024)
The worldwide transition to sustainability and responsible governance has prioritised Environmental, Social, and Governance (ESG) principles in institutional agendas. Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), as a premier technical university, has established itself as a pioneer in incorporating ESG ideals into its strategic framework. This study examines UMPSA’s mission, its conformity with ESG principles, and the possible effects of this conformity on its stakeholders and society as a whole.